Failure to report poor care as a breach of moral and professional expectation. Issue 3 (4th June 2019) - Ion, Robin; Olivier, Stephen; Darbyshire, Philip
Abstract: Cases of poor care have been documented across the world. Contrary to professional requirements, evidence indicates that these sometimes go unaddressed. For patients, the outcomes of this inaction are invariably negative. Previous work has either focused on why poor care occurs and what might be done to prevent it, or on the reasons why those who are witness to it find it difficult to raise their concerns. Here, we build on this work but specifically foreground the responsibilities of registrants and students who witness poor care. Acknowledging the challenges associated with raising concerns, we make the case that failure to address poor care is a breach of moral expectation, professional requirement and, sometimes, legal frameworks. We argue that reporting will be more likely to take place if those who wish to enter the profession have a realistic view of the challenges they may encounter. When nurses are provided with robust and applied education on ethics, when "real‐world" cases and exemplars are used in practice and when steps are taken to develop and encourage individual moral courage, we may begin to see positive change. Ultimately however, significant change is only likely to take place where practice cultures invite and welcome feedback, promote critical reflection, and where strong, clear leadership support is shown by those in positions of influence across organisations.